Pola Perlakuan Orang Tua dan Dampaknya Pada Perilaku Anak Usia Dini di Kelurahan Pisang Kecamatan Pauh Kota Padang - Wahyuni, Mitra - (Bimbingan dan Konseling, 2014)
This research is based on the phenomenon of parents who gave improper action to the children. The purpose of this study is to describe: 1) The shape of the pattern of parents treatment of children under five in developing childrenâs behavior in Kelurahan Pisang Kecamatan Pauh Kota Padang, 2) The shape of childrenâs behavior in Kelurahan Pisang Kecamatan Pauh Padang.This type of research is classified as quantitative descriptive research study. The population of this research was all parents who have. Children under five in Kelurahan Pisang Kecamatan Pauh Kota Padang with 339 peoples and the samples were 77 peoples that were taken using a simple random sampling. The instrument used in this research is a questionnaire, while for analysis data using techniques pencertage.The result of this research revealed that the pattern of treatment rejection in many categories and childrenâs behavior in good categories. The pattern of treatment acceptance in many categories and childrenâs behavior quite well categories. The pattern of submission in many categories and the categories for childrenâs behavior is good. Based on the result itâs recommended that parents need to do a treatment pattern that varies.